Multivariantna analiza zadovoljstva bolnikov z zdravnikom družinske medicine - Kersnik, Janko (Zdravniški vestnik, 2001)
Background. Patient satisfaction is an indicator of the quality of care. Methods. We used an internationally standardised and validated instrument for patients evaluations of general practice care developed in a series of studies. Sample. 60 consecutive patients in 36 practices in Slovenia were approached and offered a self-administered questionnaire. Results. I have got 84% response rate. The respondents mean age was 50 years. 64% were female, and36% male. Higher satisfaction was predicted by eight variables: higher age of the patient, higher number of office visits, aptient satisfaction with the organisation of the health care system, lower self-evaluated health status, lower number of anxiety and depression signs, not being visited in home duringout of hours services, higher number of home visits made by a family practittioner daily and active appointment system. Conclusions. The patients evaluate parts of the health care system as a whole. The survey showed necessary changes in order to improve patient satisfaction. Introduction of appointment system in primary care seems to be unavoidable. Communication skill besides family medicine curricula and vocational training in family medicine should be included in each curricula for undergraduate teaching as well in vocational training. Those who did not benefit of such training courses in communication skills should be offered. Home visits as one of the basic characteristics of family practice should be supported professionally and with financial incentives.
Keywords: bolniki; družinska medicina; Family practice; Logistic models; Multivariate analysis; Patient satisfaction; Physician-patient relations; Questionnaires; zdravstvena nega